Apoptosis in Vascular Disease - Freyssinet, Jean-Marie; Toti, Florence; Hugel, Bénédicte; Gidon-Jeangirard, Carole; Kunzelmann, Corinne; Carmen Martínez, M.; Meyer, Dominique (Thrombosis and Haemostasis, 1999)
Apoptosis, the term introduced 27 years ago to characterize a particular form of cell death distinct from necrosis,1 is now considered a genetically-controlled and energy-dependent process of fundamental significance in the development and maintenance of homeostasis in multicellular organisms.2-4 For instance, in the nematode Caenorhabditis elegans, a model widely used for the study of programmed cell death, 131 of the 1,090 somatic cells generated during hermaphrodite development undergo this form of death.5 Embryologists have suspected cell death of being instrumental in the “sculpture” of parts of the body well before the initial definition of apoptosis. In fact, cell proliferation can no longer be dissociated from apoptosis and it is obvious that variety of disorders involve either an excess of cell death for those referred to as disorders of cell loss, or a defect of apoptosis for those resulting in cell accumulation. Substantial information has been gained from studies of the hierarchical control of lymphocyte survival.6Apoptosis is accompanied by characteristic changes in cell morphology, among which shrinkage, membrane blebbing, and nucleus condensation are the most frequently evoked (Fig. 1). Budding and disintegration by fragmentation in multiple bodies is the ultimate stage of this death process.7 Alterations are induced by external signals as different as physical (radiation, mechanical stress), chemical (oxidants, xenobiotics) or biological (granzymes, receptor-mediated signals, ceramide), and also by survival factor deprivation. Interestingly, some of these signals can result from subnecrotic damage. In the so-called induction phase, each agent exerts its proapoptotic action through a “private” pathway, leading to the common pathways composed of the effector and degradation phases. The effector phase consists of a mitochondrial checkpoint involving the Bcl-2/Bax anti/proapoptotic balance, immediately after which cytochrome c is released from the injured mitochondrion and binds to adaptor proteins to activate the caspase cascade. The degradation phase is achieved by reactive oxygen species (ROS) generated at the mitochondrial level, cytoplasmic changes (depletion of glutathione and variations of cytosolic calcium), and by caspases.Caspases, also referred to as interleukin-1-converting enzyme (ICE)-like proteases, are a family of cysteine proteinases showing specificity for Asp residue and having various cytoplasmic or nuclear substrates, such as cytoskeletal proteins or proteins involved in DNA repair or control of endonucleases. The latter mechanism explains why DNA ladders, multiples of the 180 bp nucleosomal unit, constitute one of the hallmarks of apoptotic cells.8 Plasma membrane remodeling, resulting in the occurrence of phosphatidylserine (PS) in the exoplasmic leaflet and the shedding of membrane microparticles, are other hallmarks worth considering.9-12 The caspase cascade can, alternatively, be directly activated by granzyme B, which penetrates into the cytoplasm through perforin channels, or after Fas (CD95) or tumor necrosis factor (TNF) receptor 1 (TNFR1) ligation. The generation of caspase-3 (CPP32) appears to be a pivotal step, since this enzyme mediates both the activation of CAD (caspase-activated deoxyribonuclease) and PS externalization.8,13 A number of determinants, including PS, are expressed in apoptotic cells and derived fragments for their noninflammatory engulfment by phagocytes, whereas tissue necrosis is accompanied by proinflammatory events.9,11,14,15Despite extensive investigations, major gaps still exist in trying to connect and define the relative contribution of the different components of this basic process, but recently, apoptotic features have been described in unicellular, primitive eukaryotes, such as yeast,16,17 which could be used as model organisms to expand our knowledge. Owing to the presence of the effector machinery for programmed cell death in virtually all nucleated cell types, it is obvious that mechanisms have evolved in parallel for a tight regulation of apoptosis, as detailed in most of the references quoted in this section.In such an active context, the impact of apoptosis has not escaped the attention of cardiovascular biologists. Recent reviews emphasize the role of programmed cell death in cardiac development, heart failure and ischemic heart disease,18-21 and in vascular disease. Of these, a majority deal with atherosclerosis and concern endothelial or smooth muscle cells and leukocytes.22-25 To avoid redundancy, then, the purpose of the present state-of-the-art review is to focus on aspects related to plasma membrane modifications contributing to the acquisition of hemorrhagic or thrombogenic phenotypes or to the development of (auto)immune response, in vitro and in vivo, in the vascular compartment.